Comparison of Postoperative Outcomes in Colorectal Cancer Patients Undergoing Enhanced Recovery After Surgery (ERAS) vs Non-ERAS: A Retrospective Study - Erdiansyah Reza Lesmana; Ida Bagus Budhi Surya Adnyana (HM Publisher, 2025)
Colorectal cancer (CRC) represented a significant global health burden, contributing to approximately 10% of all cancer-related mortality worldwide. While surgery remained the primary treatment for resectable CRC, the postoperative period was often characterized by prolonged recovery and complications. Enhanced Recovery After Surgery (ERAS) protocols emerged as a multimodal approach to mitigate these challenges by attenuating surgical stress, optimizing nutritional status, minimizing opioid consumption, promoting early mobilization, and improving psychological well-being. This study aimed to compare the postoperative outcomes between colorectal cancer patients who underwent surgery with ERAS protocols and those who followed traditional non-ERAS recovery pathways. A retrospective cohort study was conducted at a single academic institution. The study population comprised 201 adult patients who underwent surgical resection for colorectal cancer between January 2020 and December 2024. Patients were categorized into two groups: the ERAS group (n=135), who were managed according to a standardized ERAS protocol, and the non-ERAS group (n=66), who received traditional postoperative care. Statistical analysis involved independent samples t-tests for continuous variables and chi-square tests for categorical variables, with a significance level set at p < 0.05. The ERAS group demonstrated a statistically significant reduction in the mean length of hospital stay compared to the non-ERAS group (7.67 days vs. 8.83 days, p < 0.001). While the ERAS group exhibited slightly higher mean hemoglobin levels postoperatively (11.29 g/dL vs. 11.14 g/dL, p = 0.56), this difference was not statistically significant. Notably, the incidence of postoperative complications was lower in the ERAS group (1 case) compared to the non-ERAS group (4 cases), with a p-value of 0.051, indicating a trend towards significance. In conclusion, the implementation of an ERAS protocol was associated with improved postoperative outcomes in colorectal cancer patients, specifically a significant decrease in the length of hospital stay and a trend towards a lower rate of complications. These findings supported the integration of ERAS pathways into the standard of care for colorectal cancer surgery to enhance patient recovery, potentially reduce healthcare costs, and improve overall patient outcomes.